Inhibition of poly(adenosine diphosphate-ribose) polymerase attenuates ventilator-induced lung injury - Vaschetto, Rosanna (Anesthesiology, 2008)
BACKGROUND: Mechanical ventilation can induce organ injury associated with overwhelming inflammatory responses. Excessive activation of poly(adenosine diphosphate-ribose) polymerase enzyme following massive DNA damage may aggravate inflammatory responses. We thus hypothesized that the pharmacological inhibition of poly(adenosine diphosphate-ribose) polymerase by PJ-34 will attenuate ventilator-induced lung injury. METHODS: Anesthetized rats were subjected to intratracheal instillation of lipopolysaccharide at a dose of 6 mg/kg. The animals were then randomized to receive mechanical ventilation at either low tidal volume (6 mL/kg) with 5 cmH(2)O positive end-expiratory pressure or high tidal volume (15 mL/kg) with zero positive end-expiratory pressure, in the presence and absence of intravenous administration of PJ-34. RESULTS: The high tidal volume ventilation resulted in an increase in poly (adenosine diphosphate-ribose) polymerase activity in the lung. The treatment with PJ-34 maintained a greater oxygenation and a lower airway plateau pressure than the vehicle control group. This was associated with a decreased level of interleukin-6, active plasminogen activator inhibitor-1 in the lung, attenuated leukocyte lung transmigration and reduced pulmonary edema and apoptosis. The administration of PJ-34 also decreased the systemic levels of tumor necrosis factor-α and interleukin-6, and attenuated the degree of apoptosis in the kidney. CONCLUSION: The pharmacological inhibition of poly(adenosine diphosphate-ribose) polymerase reduces ventilator-induced lung injury and protects kidney function.